2019
DOI: 10.21534/ai.v20i1.136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sacharomyces cereviceae Incorporated Diet on Growth Performance, Apparent Digestibility Coefficient of Protein and Survival Rate of Catfish (Pangasius hypothalamus)

Abstract: A new culture system is introduced to maximize diet usage for growth of Catfish (Pangasius hypothalamus). The new culture system is by incorporating Saccharomyces cerevisiae into the feed. It aims to increase feed efficiency; in turn it increases the growth of fish. The objective of the research is to know the effects of S. cereviceae incorporated diet on growth performance, apparent digestibility coefficient of protein and survival rate of catfish (P. hypothalamus). The average wight of fish used in the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…Some studies on the effect yeast (S. cerevisiae) on freshwater and marine fish have been done, such as in Barbonymus gonionotus (Rachmawati et al, 2019a), Cyprinus carpio (Al-Refaiee et al, 2016), Oreochromis niloticus (de Azevedo et al, 2016), Pangasius hypothalamus (Rachmawati et al, 2019b), Labeo rohita (Tewary & Patra, 2011), and Sarotherodon galileaus (Abdel-Tawwab et al, 2010). However, there is a lack of information about the effect of yeast (S. cerevisiae) to enhance commercial feed by increasing feed efficiency and growth of Sangkuriang catfish fingerlings.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies on the effect yeast (S. cerevisiae) on freshwater and marine fish have been done, such as in Barbonymus gonionotus (Rachmawati et al, 2019a), Cyprinus carpio (Al-Refaiee et al, 2016), Oreochromis niloticus (de Azevedo et al, 2016), Pangasius hypothalamus (Rachmawati et al, 2019b), Labeo rohita (Tewary & Patra, 2011), and Sarotherodon galileaus (Abdel-Tawwab et al, 2010). However, there is a lack of information about the effect of yeast (S. cerevisiae) to enhance commercial feed by increasing feed efficiency and growth of Sangkuriang catfish fingerlings.…”
Section: Introductionmentioning
confidence: 99%
“…The water quality was evaluated based on the previous method by Rachmawati et al (2019a). The observation of the water quality included physical and chemical characteristics of the water.…”
Section: Water Qualitymentioning
confidence: 99%
“…In addition, the supplementation of S. cerevisiae in the feed could increase the growth, immune system, and disease resistance of Oncorhynchus mykiss. Rachmawati et al (2019a) andRahmawati et al (2019b) also reported that the S. cerevisiae-supplemented feed could increase growths and survival rates of Pangasius hypothalamus and Barbonymus gonionotus. Abdel-Tawwab et al (2010), Abu-Elala et al (2013, and Manoppo and Kolopita (2016) suggested that the S. cerevisiae-supplemented feed can boost non-specific immune response and growth of tilapia (Oreochromis niloticus).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penelitian tentang penambahan ragi roti (S. cerevisiae) pada beberapa spesies ikan antara lain: ikan kerapu (Bugis dan Henky, 2014); Oreochromis niloticus (Rahman et al, 2017); Cyprinus carpio (Al-Refaiee et al, 2016); dan Pangasius hypothalamus (Rachmawati et al, 2019). Menurut Bugis dan Henky (2014), ragi roti merupakan bahan yang mengandung nukleotida yang tinggi sehingga dapat digunakan sebagai pengganti nukleotida murni.…”
Section: Pendahuluanunclassified